Metabolism of Monoterpenes : EVIDENCE FOR COMPARTMENTATION OF l-MENTHONE METABOLISM IN PEPPERMINT (MENTHA PIPERITA) LEAVES - Martinkus, Charlott (1981)
Previous studies have shown that the monoterpene ketone l-[G-(3)H]-menthone is reduced to the epimeric alcohols l-menthol and d-neomenthol in leaf discs of flowering peppermint (Mentha piperita L.), and that a portion of the menthol is converted to menthyl acetate while the bulk of the neomenthol is transformed to neomenthyl-β-d-glucoside (Croteau, Martinkus 1979 Plant Physiol 64: 169-175). The metabolic disposition of the epimeric reduction products of the ketone, which is a major constituent of peppermint oil, is highly specific, in that little neomenthyl acetate and little menthyl glucoside are formed. However, when l-[3-(3)H]menthol and d-[3-(3)H]neomenthol are separately administered to leaf discs, both menthyl and neomenthyl acetates and menthyl and neomenthyl glucosides are formed with nearly equal facility, suggesting that the metabolic specificity observed with the ketone precursor was not a function of the specificity of the transglucosylase or transacetylase but rather a result of compartmentation of each stereospecific dehydrogenase with the appropriate transferase. A UDP-glucose:monoterpenol glucosyltransferse, which utilized d-neomenthol or l-menthol as glucose acceptor, was demonstrated in the 105,000g supernatant of a peppermint leaf homogenate, and the enzyme was partially purified and characterized. Co-purification of the acceptor-mediated activities, and differential activation and inhibition studies, provided strong evidence that the same UDP-glucose-dependent enzyme could transfer glucose to either l-menthol or d-neomenthol. Determination of K(m) and V for the epimeric monoterpenols provided nearly identical values. The acetylcoenzyme A:monoterpenol acetyltransferase previously isolated from peppermint extracts (Croteau, Hooper 1978 Plant Physiol 61: 737-742) was re-examined using l-[3-(3)H]menthol and d-[3-(3)H]neomenthol as acetyl acceptors, and the K(m) and V for both epimers were, again, very similar. These results demonstrate that the specific in vivo conversion of l-menthone to l-menthyl acetate and d-neomenthyl-β-d-glucoside cannot be attributed to the selectivity of the transferases, and they clearly indicate that the metabolic specificity observed is a result of compartmentation effects.